Study the eifficiency of land transportation in the economic development under transference to the economic market, the general company of land transportation – case study – - عبد الحميد, مناهل مصطفى; احمد, محمد شهاب (Journal of Economics and Administrative Sciences, 2014)
Land Transport regards a main element in the In Fra – structure of the national economy where distance and time shortness, open new opportunities of work, develop the different regions and rise the standard of living….It is necessary to emphasize that the circumastances surrounding Iraq such as wars, economic sanctions, blockade occupation effected negatively upon economic Indicators of land Transportion including Value of output Value added contraction of Investment allocation and  Investment expend tuer and the period of implementation and fulfillment of the projects of Land Transport to be ready to offer their service in underdeveloped country Like Iraq aiming to satisfy Fast and acomprehensive development.The study aim to shed light upon the realistic of Land Transport in Iraq and its effectiveness and its role in national economy through:• Specification the present situation, importance, and development of land Transportation in all aspects.• Build Senarios for transformation toward market economy to rise its competitiveness capacities with other combinations of Transportation (Local and Foreign).The hypothesis adopted in this Study states that the Land Transportation activity in Iraq suffers a lot from the weakness of absorptive capacity and long run time lags to Invesment.